A Historical Institutionalist Framework for European Spatial Planning - Faludi, Andreas (International Planning History Society Proceedings, 2016)
Sorensen invokes historical institutionalism as a theoretical framework. This paper does so revisiting the making of the European Spatial Development Perspective of 1990s vintage and the subsequent Territorial Agenda of the European Union. The context is EU Cohesion policy. First the paper presents the theoretical framework. Then it explains why European spatial planning has been a limited success by identifying fault lines in the institutional architecture of European integration generally. The first concerns whether integration merely means states relinquishing specific powers, called competences in EU jargon, or rather whether the EU transcends states and state institutions. The second concerns whether representatives of state governments with their political and electoral concerns or the European Commission with its detached expertise should take the lead. The view that the EU has no business in planning because it is a power of the states has prevailed. To its chagrin, the Commission has also been side-lined by national planners. To overcome this problem, its idea was for the European Union to be given a competence, if not for spatial planning, then for territorial cohesion. When this came on the table, member states reconsidered their position. They adopted a Territorial Agenda of the European Union of their own. Neither their initiative nor the pursuit of territorial cohesion by the EU as such went far. Estimating that member states would not accept whatever it might propose in the matter, the Commission thus never took, as it could have done under there relevant rules an initiative in the matter. Instead it opted for a well-tried indirect approach, enlisting support from sub-national governments and also private actors. So, with its cross-border, transnational and interregional strands, ‘European territorial cooperation’ serves as a substitute for EU territorial cohesion policy proper. The paper explains the course of events over the more than twenty-five years covered by these developments by reference to the institutional architecture of the EU. The primacy which it gives to member states means that state institutions and their politics prevail over expertise, including that of planners. It also implies European space being conceptualised as a seamless cover of sovereign jurisdiction. But spatial planning within fixed borderlines flies into the face of a reality characterised by overlapping spatial networks. They cannot be contained, not even within the territory of the largest member state. So the story of European spatial planning casts a critical light on the EU institutional architecture being challenged by a fluid, dynamic spatial reality.